Simple ecological indicators benchmark regeneration success of Amazonian forests - André L. Giles; Juliana Schietti; Milena F. Rosenfield; Rita C. Mesquita; Daniel Luis Mascia Vieira; Ima C. G. Vieira; Lourens Poorter; Pedro H. S. Brancalion; Marielos Peña-Claros; João Siqueira; Luis Oliveira Junior; Mário Marcos do Espírito-Santo; et al. (Communications Earth & Environment)
Abstract Natural regeneration of Amazon forests offers a promising strategy to mitigate forest loss and advance the goals of the UN Decade on Ecosystem Restoration. However, the vast variability in regeneration rates across environmental gradients and over time poses considerable challenges for assessing regeneration success and ecosystem services provision in human-modified landscapes. Here we compiled 448 plots from forest regeneration in the Amazon to investigate the drivers of regrowth capacity and identify robust ecological indicators. By modeling optimal successional trajectories, we estimated reference values for vegetation structure, diversity, and functioning. After 20 years, successful regeneration should reach a minimum basal area of 14 m². ha−¹, at least 34 tree species per 100 individuals, a structural heterogeneity index of 0.27, and 123 Mg.ha−¹ of aboveground biomass. These straightforward indicators and reference values provide a foundational framework for governments and practitioners to assess success and establish targets for Amazon restoration efforts.